Measuring the Financial Health Performance of Life Insurance Company in Indonesia: Case Study During the Period of Before and After the Implementation of Peraturan Otoritas Jasa Keuangan, Nomor 71 /Pojk.05/2016 - Wiwiek Mardawiyah Daryanto; Wawan Rahardianto (Sekolah Tinggi Manajemen IPMI, 2019)
Insurance is simply a risk management by transferring the risk of potential loss to an insurance company. By allowing risk to be spread among a large group of people, everyone will take benefits from insurance. Therefore, selecting strong insurance company is important to make sure that your sum assured or claim will be paid according to the policy term and condition. This research aims to measure, analyze, and compare the financial health performance of public listed life insurance companies in Indonesia namely PT Prudential Life Assurance (PLA) and PT AIA Financial (AIA) from 2013 to 2018 (temporary unaudited) by using 5 financial health aspects such as Solvability Level, Technical Reserve, Investment Adequacy, Equity and Guarantee Fund as regulate by The Financial Services Authority (Otoritas Jasa Keuangan – OJK) through POJK No.71/POJK.05/2016. This research is using descriptive analysis and paired t-test to validate the differences of financial aspects during the period of before (2013-2015) and after (2016-2018) the regulation issued. The results of this study show that PLA was performing the best for solvability level, equity and guarantee fund. And PLA must enhance the performance strategy for technical reserve by gaining more premium reserves, reserve claims, reserves on PAYDI and for investment adequacy need to add more non-investment cash saving in banks reserve with the adequacy amount higher than PLA technical reserves.